Development of protocols for monitoring and preservation of mesenchymal stem cells for further clinical examination - Perepelytsina, Olena; Kopiak, Bohdan; Bezuglyi , Sergii; Sydorenko, Mykhailo (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):305